2023
DOI: 10.1302/0301-620x.105b1.bjj-2022-0465.r2
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic and radiostereometric analysis of a bicruciate-retaining versus a posterior cruciate-retaining total knee arthroplasty: a randomized controlled trial

Abstract: Aims The aim of this study was to compare a bicruciate-retaining (BCR) total knee arthroplasty (TKA) with a posterior cruciate-retaining (CR) TKA design in terms of kinematics, measured using fluoroscopy and stability as micromotion using radiostereometric analysis (RSA). Methods A total of 40 patients with end-stage osteoarthritis were included in this randomized controlled trial. All patients performed a step-up and lunge task in front of a monoplane fluoroscope one year postoperatively. Femorotibial contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Although step-up and lunge motions are regularly used in fluoroscopic studies, they are not part of (complex) daily life motions. The platform height of 18 cm high was used in previous studies [22,31]. This height, allowing 90°knee flexion in most patients, is sufficient to investigate differences in knee kinematics of TKA designs.…”
Section: Rommentioning
confidence: 99%
“…Although step-up and lunge motions are regularly used in fluoroscopic studies, they are not part of (complex) daily life motions. The platform height of 18 cm high was used in previous studies [22,31]. This height, allowing 90°knee flexion in most patients, is sufficient to investigate differences in knee kinematics of TKA designs.…”
Section: Rommentioning
confidence: 99%
“…A separate analysis of AJRR data revealed that, when compared with minimally stabilized implants (cruciate-retaining, anterior-stabilized, and pivot-bearing designs), posterior-stabilized implants had a significantly higher risk of all-cause revision (HR, 1.25; p < 0.0001) and revision for infection (HR, 1.18; p = 0.02) 41 . A bicruciate-retaining TKA design exhibits a different kinematic pattern in early flexion and late extension compared with a posterior cruciate-retaining TKA design, according to a recent report 42 . Significantly higher tibial migration was observed in the bicruciate-retaining group; as a result, longer follow-up of the newer bicruciate-retaining TKA design is warranted.…”
Section: Primary Tkamentioning
confidence: 99%
“…The understanding of the relative motion of the prosthetic components is therefore crucial to improve the sub-optimal results obtained with the first dedicated designs and assess the efficacy of the newest ones [8]. Model-based dynamic radiostereometric analysis (MB-RSA) has already been proven as a useful tool for the evaluation of total joint prosthesis kinematics in vivo and under the weight-bearing condition [9][10][11]. MB-RSA can be used to assess in vivo 3D kinematics of the prosthetic components with sub-millimetric accuracy for both rotations and translations [12].…”
Section: Introductionmentioning
confidence: 99%